Pengaruh Gaya Hidup dan Motivasi Serta Persepsi Harga Terhadap Keputusan Pembelian Handphone Merk Iphone - Amalia Wahyuni; Periyadi Periyadi; Muhammad Haris Syafitri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
Business competition is entering an era of increasingly tight competition among similar companies. This forces business actors to compete to find more effective marketing strategies. The strategies used are no longer limited to general strategies, but must be able to think creatively and innovatively, take advantage of business opportunities as much as possible and get out of the comfort zone in order to make innovations that competitors have never thought of. The purpose of this study is to determine and analyze the influence of product quality, price perception, and lifestyle on the decision to purchase iPhone products made by students of the Faculty of Economics, Islamic University of Kalimantan Muhammad Arsyad Al Banjari Banjarmasin. This study uses a quantitative method. The population in this study were UNISKA students majoring in Management, class of 2019, Banjarmasin with a total of 90 respondents. This test was carried out using the help of SPSS Statistic Software Version 26. The data collection method used a questionnaire and the data analysis technique used descriptive statistical analysis methods , instrument tests,Classical Assumption tests , multiple linear regression analysis and hypothesis tests.